Community Based Disaster Preparedness: Need for a Standardized Training Module - Garingan, Eleanor Gatchalian (International Journal of Disaster Management, 2021)
One of the biggest challenges we face today is providing information on the risk of natural disasters and preparedness is crucial with the least damage. The goal is to help develop vitally important skills and enable them to make correct decisions in critical situations. Knowledge provides the best instrument for disseminating the information necessary to reduce disaster risks by implementing appropriate risk reduction measures.This study ascertains the level of disaster preparedness in case of emergency. The study used the descriptive-correlation design with 80 respondents. Questionnaires and interviews were employed. G-Power; Frequency counts and percentages; Mean; t-test; F- test or Analysis of Variance (ANOVA) and Kendalls tau-b was used. Results revealed that the level of disaster preparedness and management in case of emergency is sometimes. Age, civil status, ethnic affiliation, and occupation affectdisaster preparedness and management in case of emergency. Ethnic affiliation and occupation affect the relationship between disaster preparedness and management in case of emergency. Findings suggest that disseminate disaster risk reduction information at all levels, develop educational programs on disaster risk reduction; develop a safe behavior model and skills, and learning by doing is necessary to develop their knowledge and skills.